JDP2: An oncogenic bZIP transcription factor in T cell acute lymphoblastic leukemia - Mansour, Marc R. (J Exp Med, 2018)
A substantial subset of patients with T cell acute lymphoblastic leukemia (T-ALL) develops resistance to steroids and succumbs to their disease. JDP2 encodes a bZIP protein that has been implicated as a T-ALL oncogene from insertional mutagenesis studies in mice, but its role in human T-ALL pathogenesis has remained obscure. Here we show that JDP2 is aberrantly expressed in a subset of T-ALL patients and is associated with poor survival. JDP2 is required for T-ALL cell survival, as its depletion by short hairpin RNA knockdown leads to apoptosis. Mechanistically, JDP2 regulates prosurvival signaling through direct transcriptional regulation of MCL1. Furthermore, JDP2 is one of few oncogenes capable of initiating T-ALL in transgenic zebrafish. Notably, thymocytes from rag2:jdp2 transgenic zebrafish express high levels of mcl1 and demonstrate resistance to steroids in vivo. These studies establish JDP2 as a novel oncogene in high-risk T-ALL and implicate overexpression of MCL1 as a mechanism of steroid resistance in JDP2-overexpressing cells.